Umoja: A Swahili feminist ethic for negotiating justice in Zanzibar. Issue 2 (2nd March 2022) - Ott, Jessica
Abstract: This article explores umoja, a Swahili worldview of relational personhood, as an alternative cultural form to rights‐based approaches for seeking gender justice in Zanzibar. Since the colonial era, umoja— which translates roughly as "unity"—has become increasingly gendered in political discourse and used by various civil society and government groups to negotiate diverse visions of gender justice. Based on ethnographic observation of a women's savings cooperative, or vicoba, of working‐class women migrants from the Tanzanian mainland, and a feminist civil society coalition, this work explores umoja as a form of feminist solidarity and as a feminist ethic. As a type of feminist solidarity, umoja is exemplified by the vicoba, which maintains relational dignity among members and structurally mitigates within‐group inequities. As a feminist ethic, umoja involves intricately negotiating subgroup interests amidst constantly shifting individual and group relationships while maintaining conviviality in larger collectivities. By prioritizing collective conviviality, umoja avoids directly confronting patriarchal social structures, which raises questions about its potential to ensure gender justice. However, its emphasis on conviviality also acknowledges a shared humanity, which together with its treatment of inequities as intersectional and relational make umoja a holistic complement or alternative to rights‐based approaches for ensuring gendered social change.